Excessive β-Catenin in Excitatory Neurons Results in Reduced Social and Increased Repetitive Behaviors and Altered Expression of Multiple Genes Linked to Human Autism - Alexander, Jonathan Michael; Pirone, Antonella; Jacob, Michele H. (Frontiers in Synaptic Neuroscience, 2020)
Multiple human autism risk genes are predicted to converge on the β-catenin (β-cat)/Wnt pathway. However, direct tests to link β-cat up- or down-regulation with autism are largely lacking, and the associated pathophysiological changes are poorly defined. Here we identify excessive β-cat as a risk factor that causes expression changes in several genes relevant to human autism. Our studies utilize mouse lines with β-cat dysregulation in forebrain excitatory neurons, identified as cell types with convergent expression of autism-linked genes in both human and mouse brains. We show that mice expressing excessive β-cat display behavioral and molecular changes, including decreased social interest, increased repetitive behaviors, reduced parvalbumin and altered expression levels of additional genes identified as potential risk factors for human autism. These behavioral and molecular phenotypes are averted by reducing β-cat in neurons predisposed by gene mutations to express elevated β-cat. Using next-generation sequencing of the prefrontal cortex, we identify 87 dysregulated genes that are shared between mouse lines with excessive β-cat and autism-like behaviors, but not mouse lines with reduced β-cat and normal social behavior. Our findings provide critical new insights into β-cat, Wnt pathway dysregulation in the brain causing behavioral phenotypes relevant to the disease and the molecular etiology which includes several human autism risk genes.